Den uhelbredeligt hjemløse kinesiske dagbogsfiktion: Om Lu Xuns og Ding Lings sygdomsramte dagbogsskrivere - Sørensen, Bo Ærenlund (K&K - Kultur og Klasse, 2021)
This article examines the disease motif in Lu Xun’s “Diary of a Madman” (1918) and in Ding Ling’s “Miss Sophia’s Diary” (1928) in their historical and medical contexts. At its most fundamental, the contemporaneous Chinese conception of health was thermodynamic, vesting the utmost importance in the circulation of energies and substances. This conception had immense social importance because it provided part of the ideological scaffolding for the family structure. Inside the family, established responsibilities and hierarchies purportedly served to guide this circulation in ways supportive of health, and the same considerations charged family members with maintaining strict scrutiny of the family’s barriers against any potentially illness-inducing influences that might penetrate the family fortress. Written at a time when political, social, and scientific verities were crumbling in China, these diaries record the foibles and concerns of two diseased individuals who stand alienated from their families and their immediate surroundings. By focusing on this alienation, as well as on the shared interests of the diarists in boundary crossing flows and anthropophagy, this article suggests that these short stories can profitably be read as explorations of the anxieties facing this generation of young Chinese as they sought to make a world for themselves independently of their families. What these stories dramatize is that leaving the family behind might have medical ramifications in addition to social and financial costs. In the current covid-19 context, we may not need reminding that ideas about disease and health relate in important ways to how we think of the relationship between families, boundaries, and vulnerability.